Mycophilic degree among the Wixaritari and mestizos in Villa Guerrero, Jalisco, Mexico - Haro-Luna, Mara Ximena; Guzmán-Dávalos, Laura; Ruan-Soto, Felipe (Ethnobiology and Conservation, 2020)
The appreciation and taste towards mushrooms are influenced by sociocultural factors and ecological variables. This study evaluated the mycophilic degree among the Wixaritari and mestizo communities in a municipality in the north of Jalisco, settled in different types of vegetation, to determine if ecological and sociocultural factors influence the attitude towards the mushrooms. The Mycophilia-Mycophobia Index was evaluated in 10 communities in which semi-structured interviews were conducted with a representative number of people. Responses to 18 indicators were analyzed by χ2 test and multivariate techniques. To determine which factors best explain the observed attitudes, six models were constructed using a Beta probability-density function with maximum likelihood adjustment; finally, a comparison using the Akaike Information Criterion was made. In general, the population resulted mycophilic; the χ2 test showed that there were significant differences between the Wixaritari and mestizo attitudes in 10 of the 18 indicators. In the ordination and classification analyses, the communities did not cluster by cultural group or vegetation, and one mestizo community was isolated from the others. The model that best explains the mycophilic attitudes was community-cultural group in which the vegetation was involved. One Wixarika community in pine forest was extremely mycophilic, in contrast to a mestizo community in oak forest that was indifferent to the mushrooms; these attitudes were the result of historical events that have modified the lifestyle of people. The differences in the evaluated indicators were due to the cosmovision of each cultural group.